Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.7326/0003-4819-136-8-200204160-00007
|View full text |Cite
|
Sign up to set email alerts
|

High Risk for Hyperlipidemia and the Metabolic Syndrome after an Episode of Hypertriglyceridemia during 13-cis Retinoic Acid Therapy for Acne: A Pharmacogenetic Study

Abstract: Persons who develop hypertriglyceridemia during isotretinoin therapy for acne, as well as their parents, are at increased risk for future hyperlipidemia and the metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
51
1
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 15 publications
8
51
1
5
Order By: Relevance
“…15 The increase in triglyceride levels in patients being treated with oral isotretinoin may be related to a reduction in the removal rate of these lipids from plasma. 23 It also appears to be influenced by the increase in gene expression for Apo E. 24 In agreement with reports from other studies, no correlation was found between the oral dose of isotretinoin and the increase in triglycerides. 12,25 Furthermore, there appears to be no correlation between the cumulative dose of isotretinoin and the magnitude of the increase in triglycerides.…”
Section: Discussionsupporting
confidence: 85%
“…15 The increase in triglyceride levels in patients being treated with oral isotretinoin may be related to a reduction in the removal rate of these lipids from plasma. 23 It also appears to be influenced by the increase in gene expression for Apo E. 24 In agreement with reports from other studies, no correlation was found between the oral dose of isotretinoin and the increase in triglycerides. 12,25 Furthermore, there appears to be no correlation between the cumulative dose of isotretinoin and the magnitude of the increase in triglycerides.…”
Section: Discussionsupporting
confidence: 85%
“…5,6 Rodondi et al identified a propensity to develop the metabolic syndrome in patients who had a pronounced elevation in TG levels during use of oral isotretinoin, suggesting the participation of genetic factors. 7 These correlations may help explain the apparent propensity of women to develop high TG levels, as found in the present study, particularly in adult women with persistent acne. Possible inconsistencies in data that are inherent to retrospective studies may have affected the present findings.…”
Section: Comunicationsupporting
confidence: 65%
“…23 This study shows the PD/Cub strain to be sensitive to modulation of triglyceride concentrations by isotretinoin, a phenomenon previously noted not only as a side effect of the treatment aimed at mostly dermatological disorders, 5 but also as a possible pharmacogenetic indicator of hereditary proneness to familial combined hyperlipidemia and metabolic syndrome. 24 Moreover, the increased adiposity and insulin resistance of skeletal muscle tissue in the isotretinoin-treated group are well in consent with the adverse reactions seen in the sensitive human subjects. 24 Therefore, this strain may well serve as a tool for dissection of the genetic component involved in the described pharmacogenetic interaction.…”
Section: Discussionmentioning
confidence: 84%
“…24 Moreover, the increased adiposity and insulin resistance of skeletal muscle tissue in the isotretinoin-treated group are well in consent with the adverse reactions seen in the sensitive human subjects. 24 Therefore, this strain may well serve as a tool for dissection of the genetic component involved in the described pharmacogenetic interaction. The mechanism of retinoic acid induced hypertriglyceridemia is unknown.…”
Section: Discussionmentioning
confidence: 84%